A USER ACCEPTANCE FRAMEWORK FOR THE ONLINE TEACHING EFFICIENCY RATING SYSTEM OF MINDANAO STATE UNIVERSITY-ILIGAN INSTITUTE OF TECHNOLOGY - vistal, jogie; Sala, Erik Louwe (International Journal of Multidisciplinary Research and Studies, 2022)
The researchers in the field of Information Technology and Information System are of interest in understanding the factors in user acceptance of a new technology. Unified Theory of Acceptance and Use of Technology (UTAUT) is one of the prominent models used in determining the factors of the user acceptance of technology. In this research, the four constructs of the Unified Theory of Acceptance and Use of Technology (UTAUT) was used namely: Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI) and Facilitating Conditions (FC) and associating the user satisfaction to the four constructs of the UTAUT. Survey was used for this inquiry. For data analysis Cronbachs’s Alpha was used to check the reliability of the instrument, weighted mean was applied to determine the level of the user satisfaction, Correlation Coefficient technique was utilized to predict UTAUT factors and Somer’s delta was used to determine the strength of PE, EE, SI and FC to S. The outcome of this research is the user acceptance framework for the Online Teacher Efficiency Rating of Mindanao State University- Iligan Institute of Technology (MSU-IIT), Iligan City, Philippines. The computed t-test and its associated p–values presented suggest that the independent variables such as PE, EE and FC are statistically significant. Hence, the three constructs affect the user satisfaction.